DEVICES THAT ENABLED REMOTE MONITORING OF PATIENTS' HEALTH CONDITIONS WERE BECOMING MORE SOPHISTICATED - Khalid Fahad Al Harbi, Mustafa Abdulrahman Sahal Alotaibi, Defallah Hamoud Almutairi , (Chelonian Research Foundation, 2024)
The development of devices for remote patient monitoring has been steadily advancing, allowing for more sophisticated monitoring of patients' health conditions. This essay explores the evolution of remote monitoring devices, the methodologies used in this field, as well as the results and implications of this technology. Through a comprehensive analysis of the current landscape of remote patient monitoring devices, this essay seeks to shed light on the potential benefits and challenges associated with these technologies.